1998
DOI: 10.1001/archpedi.152.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke and Middle Ear Disease in Preschool-Age Children

Abstract: To determine the association between environmental tobacco smoke and middle ear disease in preschool-age children. Design: A population-based case-control study with verification of disease history and exposure reporting in a subsample. Setting and Participants: Participants were identified through a population-based probability sample of 1320 first-grade students in 36 schools in Calgary, Alberta. The parents of 625 children meeting case (n=227) or control (n=398) definitions were interviewed by telephone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 44 publications
1
51
0
4
Order By: Relevance
“…A fumaça domiciliar do tabaco é o mais comum poluidor do ar doméstico, podendo variar sua concentração de acordo com o núme-ro de fumantes do domicílio e do número de cigarros fumados dentro de casa, estando associada a vários desfechos desfavoráveis à saú-de infantil 9,10 .…”
Section: Introductionunclassified
“…A fumaça domiciliar do tabaco é o mais comum poluidor do ar doméstico, podendo variar sua concentração de acordo com o núme-ro de fumantes do domicílio e do número de cigarros fumados dentro de casa, estando associada a vários desfechos desfavoráveis à saú-de infantil 9,10 .…”
Section: Introductionunclassified
“…A literatura tem mostrado que, das manifestações otorrinolaringológicas, as otites média, aguda ou crônica são as principais queixas das crianças relacionadas à exposição ambiental do cigarro (21,24,(39)(40)(41) . É importante salientar que o critério adotado neste estudo foi um diagnóstico "referido" e, para maior confiabilidade, foi decidido que apenas os casos confirmados por médicos seriam considerados como portadores da doença.…”
Section: Discussionunclassified
“…Em relação às infecções do trato respiratório superior, elas constituem um importante problema de saúde públi-ca, devido a sua elevada prevalência, sendo o principal motivo de consulta médica no primeiro ano de vida e a maior taxa de absenteísmo escolar (18,20,21) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Tobacco smoke is a well-documented toxic air contaminant that contributes to increased morbidity and mortality in children. It leads to a greater likelihood of lower respiratory infections, [2][3][4] sudden infant death syndrome, 5,6 and ear infections, 7 and it increases the severity of asthma symptoms. 8,9 In 1992, the US Environmental Protection Agency concluded that TSE is a "group A" carcinogen, a substance that has been established as a definitive cause of cancer in humans.…”
mentioning
confidence: 99%